2018
DOI: 10.1038/s41576-018-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Coaching from the sidelines: the nuclear periphery in genome regulation

Abstract: The genome is packaged and organized nonrandomly within the 3D space of the nucleus to promote efficient gene expression and to faithfully maintain silencing of heterochromatin. The genome is enclosed within the nucleus by the nuclear envelope membrane, which contains a set of proteins that actively participate in chromatin organization and gene regulation. Technological advances are providing views of genome organization at unprecedented resolution and are beginning to reveal the ways that cells co-opt the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 167 publications
(252 reference statements)
2
147
0
Order By: Relevance
“…In order for a dividing cell of a given lineage to maintain its identity, it must pass along to its 2 progeny not only a complete copy of its genome, but also the memory of its specific cellular 3 identity (Buchwalter et al, 2019, Towbin et al, 2013, Amendola and van Steensel, 2014. It is transcriptional repression.…”
Section: Introductionmentioning
confidence: 99%
“…In order for a dividing cell of a given lineage to maintain its identity, it must pass along to its 2 progeny not only a complete copy of its genome, but also the memory of its specific cellular 3 identity (Buchwalter et al, 2019, Towbin et al, 2013, Amendola and van Steensel, 2014. It is transcriptional repression.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in understanding how the heterochromatin compartment is organized at the nuclear envelope, and how lineage-inappropriate genes are silenced through such positioning (Amendola and van Steensel, 2014;Buchwalter et al, 2019;Gordon et al, 2015;Gruenbaum and Foisner, 2015;Harr et al, 2016;Lemaitre and Bickmore, 2015;Meister and Taddei, 2013;Padeken and Heun, 2014;Poleshko et al, 2017;Politz et al, 2013;Shevelyov and Nurminsky, 2012;Shevelyov and Ulianov, 2019;Ungricht and Kutay, 2015;van Steensel and Belmont, 2017;Wong and Reddy, 2015;Yanez-Cuna and van Steensel, 2017;Zullo et al, 2012). Emerging research findings have pointed to an evolutionarily conserved mechanism whereby a class of three "tethering proteins" function to organize H3K9me-modified heterochromatin at the nuclear periphery (Gonzalez-Sandoval et al, 2015;Harr et al, 2016;Kind et al, 2013;Poleshko et al, 2013;Towbin et al, 2013;van Steensel and Belmont, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The eukaryotic DNA genome is organized into chromatin and is enclosed by the nuclear envelope that forms the border of the nuclear organelle. The nuclear envelope is a double membrane (Buchwalter et al, 2019;Hetzer, 2010;Ungricht and Kutay, 2015) that in multicellular organisms, includes the nuclear lamina protein framework that lies underneath the inner nuclear membrane (Dittmer and Misteli, 2011;Gruenbaum and Foisner, 2015). The nuclear lamina is composed of the intermediate filament proteins Lamin A/C, Lamin B1 and Lamin B2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have utilized chromosome conformation capture techniques like 3-C and Hi-C to infer 3D genome organization by analyzing interaction frequencies between different regions of the genome [96]. Such studies have revealed a genome organization in which chromosomes occupy distinct territories in nuclear space and then fold into gene-rich and transcriptionally active or gene-poor & transcriptionally repressed compartments (referred to as A and B compartment respectively) [97]. These compartments are further divided into topologically associated domains (TADs) that are enriched for local genomic interactions and conserved across cell types and species.…”
Section: Neurogenesis As a Paradigm To Study The Role Of Actin In Genmentioning
confidence: 99%